Real Time Operation Simulation Model with Early Release Reservoir Storage - Ida W. Amitaba; Pitojo T. Juwono; Lily M. Limantara; Runi Asmaranto (Journal of Human, Earth, and Future)
This research intends to build an optimal curve model of reservoir water level fluctuation for real-time water supply operation and to build an information system of gate opening operation due to the real-time release of reservoir storage by considering water demand and flood capacity in the downstream. The proposed methodology combines the update of an optimized rule curve forecast based on 10-dayly inflows projected for the next three months and the optimization of early release volumes based on hourly reservoir routing inflows over the upcoming two days. The water balance simulation is conducted to optimize the irrigation water release-to-demand ratio (K Factor) by considering both deterministic and stochastic inflow scenarios. Real-time reservoir routing simulation is performed to optimize gate openings with the constraint of maintaining the end-of-period water level in line with the updated ten-daily rule curve forecast. This research is conducted in the Dodokan Watershed with the cascade reservoir of Batujai and Pengga. Simulations indicate that optimized gate openings—two gates at 0.4 m and two at 0.2 m for Batujai (with an inflow of 638.7 m³/s) and 0.3 m on Pengga's sixth gate (with an inflow of 616.3 m³/s)—effectively prevent downstream flooding, maintaining reservoir levels within safe limits under High Flood Water Levels (HFLW) and ensuring water supply continuity. With an average K factor effectiveness of 83% for stochastic inflow prediction and 79% for deterministic inflow prediction, the optimized model adjusts spillway operations in real time, ensuring enhanced flood control and operational safety by aligning with real-time rule curves.